Post-traumatic epilepsy: bridging pathogenesis, diagnosis, and pharmacotherapeutic strategies - Yang, Xiaoyu; Chen, Siyang; Wang, Haozhou; Sun, Tong; Wu, Ke (Frontiers in Pharmacology, 2025)
Post-traumatic epilepsy (PTE)—affecting 2%–50% of traumatic brain injury (TBI) survivors with severity-dependent incidence—drives secondary neurodegeneration through elevated intracranial pressure (ICP), axonal injury, and neuroinflammatory cascades. While integrated risk stratification (e.g., cortical contusion, acute subdural hematoma on CT; blood-brain barrier disruption via dynamic contrast-enhanced MRI) enhances epileptogenesis prediction, mechanistic understanding of circuit reorganization underlying chronic hyperexcitability remains incomplete. Diagnosis integrates trauma history, seizure semiology, and multimodal monitoring (high-density EEG correlated with [18F] FDG-PET hypometabolism), yet evidence-based prophylaxis is confined to early PTE prevention. In this review, we will describe the progress in incidence, predictors, pathophysiological mechanisms diagnosis, prophylaxis, and treatments with the respect to PTE, providing a comprehensive overview of this subject.